An efficient continuous phase modulation for high data rate body area networks. (1st January 2012) - Panda, Rutuparna; Rout, Deepak Kumar
This paper presents a novel modulation technique for body area networks. The new modulation technique is designed taking into account the Rayleigh nature of body area channel. In this paper, we propose a novel idea that combines properties of continuous phase modulation and pulse position modulation techniques. Simulation is carried out at different frequencies on this channel. A comparison is presented between the existing modulation techniques like the m-ary PSK and FSK and the special modulation techniques proposed for body area networks (BANs). The proposed technique is highly immune to multipath distortion and fading. Apart from being power efficient, the technique does not demand large bandwidth compared to its counterparts. The benefit of the proposed modulation technique lies in its ability to carry large number of bits per symbol. Another advantage is its ability to carry maximum information while signal is null. This method is useful to support high data rate for wireless body area networks.